Epithelial implantation treatment after small-incision lenticule extraction. Issue 4 (April 2020) - Piccinini, Paola; Vida, Ryan S.; Piccinini, Renato; Maiore, Irene; Archer, Timothy J.; Carp, Glenn I.; Reinstein, Dan Z.
Abstract : Epithelial implantation after SMILE can be successfully treated by sweeping and washing out the interface or Nd:YAG laser. Abstract : Two cases of epithelial implantation after small-incision lenticule extraction (SMILE) treated by Nd:YAG laser and interface sweeping are described. A 40-year-old woman and 33-year-old man underwent SMILE and subsequently were noted to have epithelial cells implanted into the surgical interface. One case was treated using Nd:YAG laser. The laser was focused to the level of the interface with an energy level of 0.3 mJ. The treatment covered the entire area of epithelial implantation. The second case was treated by opening the original SMILE incision and sweeping the residual epithelial cells from the interface followed by a washout. Both the Nd:YAG laser and interface sweeping proved to be effective in reducing or eliminating the epithelial cells from the SMILE interface. Further studies are needed to report on overall safety and efficacy of these 2 techniques.